2013
DOI: 10.1021/jp407282c
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Significance of Water Clusters and Ozone–Water Complexes

Abstract: Ozone-water complexes O3···(H2O)n (n = 1-4) have been theoretically investigated using QCISD and CCSD(T) methods along with the 6-311G(2df,2p), 6-311+G(2df,2p), aug-cc-pVDZ, aug-cc-pVTZ, and aug-cc-pVQZ basis sets and extrapolation to CBS limit. For comparison, water clusters (H2O)n (n = 1-4) have also been studied at the same level of theory. The ozone-water complexes are held together by a combination of weak specific hydrogen-bonding and van der Waals interactions. Surprisingly, the hydrogen-bonded complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 120 publications
3
98
1
Order By: Relevance
“…There have been a small number of studies which employed more appropriate methodologies, e.g., quadratic configuration interaction with single and double excitations (QCISD), coupled-cluster with singles and doubles and linked triples (CCSD(T)), and/or multi-configurational methods, 13,14 but most of these have focused on complexes between O 3 and H 2 O. [15][16][17] Within the experimental context, in their study of the O· · ·O 3 complex through O 3 generation with photolysis of an oxygen matrix at 11 K, Schriver-Mazzuoli et al observed a peak at λ = 360 nm for the photodissociation of the (O 3 ) 2 dimer, but did not provide any structure. 18 Later, in 2001, Bahou et al 19 studied the IR spectroscopy and photochemistry at 266 nm of (O 3 ) 2 trapped in an argon matrix and cona) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a small number of studies which employed more appropriate methodologies, e.g., quadratic configuration interaction with single and double excitations (QCISD), coupled-cluster with singles and doubles and linked triples (CCSD(T)), and/or multi-configurational methods, 13,14 but most of these have focused on complexes between O 3 and H 2 O. [15][16][17] Within the experimental context, in their study of the O· · ·O 3 complex through O 3 generation with photolysis of an oxygen matrix at 11 K, Schriver-Mazzuoli et al observed a peak at λ = 360 nm for the photodissociation of the (O 3 ) 2 dimer, but did not provide any structure. 18 Later, in 2001, Bahou et al 19 studied the IR spectroscopy and photochemistry at 266 nm of (O 3 ) 2 trapped in an argon matrix and cona) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies focused on the reactions without a surrounding molecule and with only one surrounding molecule. Thus, through AIMD simulations, we further investigated the cases with multiple water molecules to account for the reactions occurring in clusters and droplets in the atmosphere . The reactions with 3–5 and 34 H 2 O molecules were studied successively, and all the reactions leading to the formation of NH 4 HSO 4 were observed soon after starting each simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen-bondedsmall-moleculeclustersinthegas,liquid, and solid states have been studied extensively because they play asignificant role in various chemical, environmental, and biological processes,a nd the greatest interest is attracted by clusters of water as the most important biological molecule. [1][2][3][4][5][6][7] Among other tiny molecular species hydrogen peroxide is the closest relative of water and is also involved in many significant environmental and biological phenomena. [8][9][10] It was recently shown that hydrogen peroxide forms noticeably stronger H-bonds than water in isomorphous peroxosolvates-hydrates.…”
mentioning
confidence: 99%